Application of Antibiotics/Antimicrobial Agents on Dental Caries. (31st January 2020) - Qiu, Wei; Zhou, Yujie; Li, Zixin; Huang, Tu; Xiao, Yuhan; Cheng, Lei; Peng, Xian; Zhang, Lixin; Ren, Biao
Abstract : Dental caries is the most common oral disease. The bacteriological aetiology of dental caries promotes the use of antibiotics or antimicrobial agents to prevent this type of oral infectious disease. Antibiotics have been developed for more than 80 years since Fleming discovered penicillin in 1928, and systemic antibiotics have been used to treat dental caries for a long time. However, new types of antimicrobial agents have been developed to fight against dental caries. The purpose of this review is to focus on the application of systemic antibiotics and other antimicrobial agents with respect to their clinical use to date, including the history of their development, and their side effects, uses, structure types, and molecular mechanisms to promote a better understanding of the importance of microbial interactions in dental plaque and combinational treatments.